Analisis Fundamental Perusahaan LQ45 Tahun 2024: Hubungan EPS dan PBV dengan Harga Saham - Aflaha, Vini Annesia; Dwiyanti, Yeni Hilma (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study aims to examine the influence of Earnings per Share (EPS) and Price to Book Value (PBV) on stock prices of companies listed in the LQ45 Index on the Indonesia Stock Exchange in 2024. The background of this research is based on the substantial fluctuations in stock prices during the 2024 period, reflecting unstable global and domestic economic conditions. A quantitative approach with a causal associative research design was employed. The population consisted of all companies included in the LQ45 Index, and a total of 45 companies were selected as the sample using purposive sampling. The study used secondary data obtained from annual financial statements and stock price information published by the Indonesia Stock Exchange. Data were analyzed using multiple linear regression with SPSS, preceded by classical assumption tests (normality, multicollinearity, and heteroscedasticity tests). The results indicate that EPS has a positive and significant effect on stock prices, with a significance value of 0.000 and a regression coefficient of 0.476, meaning that higher earnings per share lead to increased stock prices. PBV also shows a positive coefficient of 0.306 but is not statistically significant, with a significance value of 0.147, implying that PBV does not have a partial effect on stock prices, although market valuation relative to book value still shapes investor perception. The simultaneous test demonstrates that EPS and PBV jointly have a significant effect on stock prices, with a significance value of 0.000 and an adjusted R² of 0.618, indicating that the model explains 61.8% of stock price variation, while the remaining 38.2% is influenced by other factors outside the model. Overall, the findings confirm that EPS is the most decisive fundamental indicator in determining the stock prices of LQ45 companies. These results reinforce that fundamental factors continue to play a crucial role in shaping market valuation in Indonesia.